Rio arraias: uma análise do potencial turístico - Santos, Sandra Ferreira dos (Universidade Federal do Tocantins, 2021)
Answering the questions "What does Arraias have to offer for the tourist?", "What exists in matter of waterfalls in the rivers of the municipality, that can foment the development of ecotourism?", is an important step for the organization and development of local tourism and, consequently, to promote the increase of social opportunities, the competitiveness of the local economy and the generation of employment and income without, however, neglecting the conservation of natural resources. Cities with already structured tourism are able to fit in the market and attract many tourists, since they have a variety of well-known and structured occupations that can be explored by visitors. In this context, the main objective of this work was to map and evaluate natural attractions with possibilities for ecotourism practice and to identify signs of environmental degradation in the Arraias River, in the municipality of Arraias -TO, in a 10 km course, starting from the site known as ". This work makes a qualitative approach to present the results obtained, and can be classified as descriptive research. The field incursions identified 42 points with potential for ecotourism activity development. Of these 42 points, 7 (seven) were identified as waterfalls, 6 (six) waterfalls and 29 (twenty-nine) wells. The anthropic activities identified in the study area were deforestation, pasture, fire and garbage.